PENGARUH WORD OF MOUTH DAN BRAND IMAGE TERHADAP KEPUTUSAN PENGGUNAAN SALON KECANTIKAN PADA KONSUMEN MILOFF BEAUTY BAR - Finanda, Iknesya Rahma; Wiwaha, Arjuna (L2Dikti Wilayah III, 2018)
Miloff Beauty Bar is a beauty salon that is a place of life style, where consumers can get quality and satisfactory beauty services by professional and friendly therapists in a comfortable and clean environment. This research discusses the problem of word of mouth and brand image influence on purchasing decision. The purpose of this study is to determine the effect of word of mouth and brand image simultaneously to the purchase decision. Research method used library research and field research. The research was conducted at Miloff Beauty Bar Jakarta. The time of the study from April to August 2017. The sample in this study amounted to 78 customers. Techniques used in collecting data is the spread of questionnaires, interviews and observation. This study uses SPSS to calculate and analyze data. The results of this study show that word of mouth and brand image simultaneously have a positive and significant effect on purchasing decisions.